Promotive and Preventive Programs for Health Workers and Mothers on Newborn Umbilical Cord Care to Prevent Infection During the Neonatal Period - Wahyuni, Fera; Lubis, Syamsidah; Faradina, Dwi; Husada, Muhammad Surya (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Umbilical cord infections can be prevented by caring for the umbilical cord properly. The data regarding proper and correct umbilical cord care of newborn babies by mothers in North Sumatra Province is limited. Hence, this community service aimed to determine the proportion of knowledge in umbilical cord care for newborn babies using the open-dry cord care method. Thew community service project was held on August 24, 2023, in Pematang Siantar City, North Sumatra Province. In this activity, we provided counseling on the open-dry cord care method for umbilical cord care by presentation and discussion using modules, posters, and leaﬂets. We used a pre-test and post-test questionnaire to assess the knowledge level of health workers and mothers. Participant demographic data and results are presented in the form of proportion data. This counseling was attended by 150 participants consisting of 52 health workers and 98 mothers. Before the counseling, 39 health workers and 93 mothers did not know how to take care of the umbilical cord properly. After the counseling, the knowledge of umbilical cord care using the open-dry cord method increased by 15.4% for health workers and 24.5% for mothers. Based on the results, over 80% of participants were found to have had a satisfactory level of knowledge about umbilical cord care after the counseling session. This community service program should be conducted regularly to further enhance the knowledge of health workers and mothers on proper umbilical cord care.